2011
DOI: 10.1080/17461391.2011.566357
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a short physical activity recall questionnaire completed by Spanish adolescents

Abstract: Self-report recall questionnaires are commonly used to measure physical activity in children and adolescents. However, they have been shown to have low to moderate validity, mainly due to inaccuracies in recall activity. The purpose of the present study was to determine the reliability and validity of an adapted version of the Assessment of Physical Activity Levels Questionnaire (APALQ) among a sample of Spanish adolescents. TestÁretest reliability of the APALQ was assessed using a sample of 150 adolescents (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 50 publications
0
16
0
2
Order By: Relevance
“…Previous studies in pediatric populations have reported similar results , but the limitation in these studies is that the authors evaluated only one city, whereas our study was conducted in seven South American cities for reliability and in four for validity. Questionnaire‐based vigorous PA was strongly associated with test‐retest reliability in both age groups and with concurrent validity against an accelerometer in adolescents.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Previous studies in pediatric populations have reported similar results , but the limitation in these studies is that the authors evaluated only one city, whereas our study was conducted in seven South American cities for reliability and in four for validity. Questionnaire‐based vigorous PA was strongly associated with test‐retest reliability in both age groups and with concurrent validity against an accelerometer in adolescents.…”
Section: Discussionmentioning
confidence: 69%
“…For validity, the intensity (moderate and vigorous) and total (summary of the three domains) were analyzed. A moderate Spearman correlation (ρ ≥ 0.30) and kappa coefficient (k ≥ 0.40) were considered acceptable. Stata software version 14.0 (StataCorp, College Station, Texas) was used for all statistical analyses.…”
Section: Methodsmentioning
confidence: 99%
“…However, again, the study quality could not be assessed due to the minimal amount of information provided. Lastly, 15 of the questionnaires were translated versions [ 33 , 35 , 39 , 40 , 43 , 46 53 ]; the majority of these studies provided little information on the translation processes. These studies did not assess the cross-cultural validity, and thus no definite conclusion about the content validity of the translated questionnaires could be drawn.…”
Section: Resultsmentioning
confidence: 99%
“…PAR hours r 0.51; vs. activity rating r 0.73; vs. Godin 1 r 0.57; vs. Godin 2 r − 0.62 3 of 5 hypotheses correct Fair (all comparison measures) Level 1: – Modified Physical Activity Questionnaire for Adolescents (PAQ-A) [ 34 ] n = 88 Age: 14.5 ± 1.7 years Sex: 42% girls (Age and sex total sample n = 169) Acc. (Actigraph) (cut-points not reported) IFIS (Fitness) PAQ-A total score: vs. daily MVPA min/day SCC 0.39; vs. daily PA min/day SCC 0.42 Sport and activity list: vs. daily MVPA min/day SCC 0.12; vs. daily PA min/day SCC 0.21 Before school activity: vs. daily MVPA min/day SCC 0.02; vs. daily PA min/day SCC 0.14 To school active travel: vs. daily MVPA min/day SCC 0.32; vs. daily PA min/day SCC 0.33 PE: vs. daily MVPA min/day SCC 0.25; vs. daily PA min/day SCC 0.12 After-school activity: vs. daily MVPA min/day SCC 0.26; vs. daily PA min/day SCC 0.26 From school active travel: vs. daily MVPA min/day SCC 0.30; daily PA min/day SCC 0.22 Evening activity: vs. daily MVPA min/day SCC 0.23; vs. daily PA min/day SCC 0.23 Weekend activity: vs. daily MVPA min/day SCC 0.10; vs. daily PA min/day SCC 0.28 Statement: vs. daily MVPA min/day SCC 0.38; vs. daily PA min/day SCC 0.33 Weekly activity: vs. daily MVPA min/day SCC 0.34; vs. daily PA min/day SCC 0.29 PAQ-A total score: vs. IFIS scores SCC 0.35 Fair (all comparison measures) Level 1: – Level 2: – An adapted version of the Assessment of Physical Activity Levels Questionnaire (APALQ) [ 53 ] n = 77 Age: 13.6 ± 1.1 years Sex: 35% girls Acc. (CSA) (cut-points: MPA 3000–5399 cpm; VPA > 5400 cpm) PA index: vs. acc.…”
Section: Methodsmentioning
confidence: 99%
“…Provavelmente o questionário de AF têm resultados melhores do que questionários de atividade física(20,(72)(73)(74), pois são necessárias muitas questões para investigar o constructo de interesse, o que pode levar a erros, sobreposição das respostas, redução da atenção e motivação…”
unclassified